First isolation and characterization of the prototype strain of SARS-CoV-2 at the beginning of the COVID-19 pandemic in Peru - García, María P. (2023)
Introduction: Currently, infections by the SARS-CoV-2 virus exceed 600 million cases in the world. Objective: Isolation and characterization of the SARS-CoV-2 virus causing COVID-19 at the beginning of the pandemic in Peru. Materials and methods: Twenty nasal and pharyngeal swab samples were isolated SARS-CoV-2 using two cell lines, Vero ATCC CCL-81 and Vero E-6; virus identification was performed by RT-PCR and the onset of cytopathic effect (CPE) was evaluated by indirect immunofluorescence and subsequent identification by genomic sequencing. One of the most widely circulating isolates was selected and named the prototype strain (PE/B.1.1/28549/2020). Then 10 successive passages were performed in Vero ATCC CCL-81 cells to assess mutation dynamics. Results: Results detected 11 virus isolates by cytopathic effect, and subsequently confirmed by RT-PCR and indirect immunofluorescence. Of these, six were sequenced and identified as the lineages B.1, B.1.1, B.1.1.1, and B.1.205 according to the Pango lineage nomenclature. The prototype strain corresponded to lineage B.1.1. The analysis of the strains from the successive passages showed mutations mainly at in the spike (S) protein of the virus without variation in the identity of the lineage. Conclusions: Four lineages were isolated in the Vero ATCC CCL-81 cell line. Subcultures in the same cell line show mutations in the spike protein indicating greater adaptability to the host cell and variation in pathogenicity in vitro, a behavior that allows it to have more survival success.